Dumping in Developing and Transition Economies - Jose Luis Moraga-Gonzalez; Jean-Marie Viaene (Tinbergen Institute, 2004)
We build a simple theoretical model to understand why developing and transition economieshave increasingly applied anti-dumping laws. To that end, we investigate the strategic incentivesof oligopolistic exporting firms to undertake dumping in these economies. We show that dumpingmay be due to cross-country differences in income, to the extent of tariff protection and to theexchange rate depreciations observed recently. Dumping may arise even if consumers exhaustall arbitrage possibilities.
Keywords: F12; F13; P31; 330; Dumping; Exchange Rate; Optimal Thade Policy; Product Quality; Dumping; Antidumping; Übergangswirtschaft; Transformationsstaaten; Entwicklungsländer